Development of seaweed extracts-based films for application in the food sector - Trindade, Marlene Almeida (2021)
Seaweed are an abundant and sustainable source for the production of nutritious and healthy food, presenting bioactive compounds useful for several industries. Macroalgae have numerous applications, but they are still an underexploited resource that has to reach its full application potential. With consumers' increasing environmental awareness, the demand for more sustainable products is also increasing, pressuring the packaging industry to develop more sustainable alternatives to single-use plastic. There are several studies that successfully report the use of seaweed polysaccharides-based films in maintaining the properties of food products, but few are those that use seaweed extracts in the formulation of the film matrix. In this work bioactive films were developed for food applications using aqueous extracts of the brown marine macroalga Bifurcaria bifurcata and the red marine macroalgae Porphyra sp. and Osmundea pinnatifida. The composition of the initial biomass of the algae was determined in terms of polysaccharide, protein and ash content. B. bifurcata presented the highest amount of carbohydrates (50 % w/w) and inorganic material (16 % w/w), while the red macroalgae showed the highest amount of protein (29 and 31 % w/w for Porphyra sp. and O. pinnatifida, respectively). Aqueous extracts were obtained from the initial biomass, with room temperature water and hot water (90 ºC). Both red algae extracts showed an increase in the total carbohydrate content, in relation to the sugar content of the initial biomass, being similar to each other in the amount and composition of sugars. The hot water extract from B. bifurcata showed an increase in the content of sugars obtained. In addition, all extracts showed higher amounts of sulfated compounds (Porphyra sp. 12 and 10 %; O. pinnatifida 19 and 16 %; B. bifurcata 16 and 8 %) than the initial biomass and B. bifurcata extracts showed also higher amounts of soluble protein (30 and 50 %). The greatest antioxidant activity was observed for the B. bifurcata extracts followed by Porphyra sp. and O. pinnatifida. The films produced using aqueous extracts of O. pinnatifida were less resistant, less elastic and less plastic, while those of Porphyra sp. were more resistant and flexible. The contact angle results showed that Porphyra sp. have a more hydrophobic surface. However, Porphyra sp. and O. pinnatifida films are very soluble in aqueous medium, while those of B. bifurcata presented solubility values below 50%, even after 7 days immersed in water. All films showed antioxidant activity, but the brown alga had a higher value. Taking into account the characteristics of the extracts and films obtained, we can consider that we have obtained films with mechanical properties and the potential to promote food preservation due to their antioxidant capacity to be applied in the food industry, namely in the development of packaging.